2019
DOI: 10.1002/jcp.28974
|View full text |Cite
|
Sign up to set email alerts
|

The whole transcriptional profiling of cellular metabolism during adipogenesis from hMSCs

Abstract: Metabolism homeostasis plays an important role in progenitor-cell differentiation to adipocytes, but less is known about the whole transcriptional profiling of cellular metabolism during adipogenesis. We got the first insight into the whole transcriptional profiling of cellular metabolism during adipogenesis from human mesenchymal stem cells (hMSCs) by the RNA-Seq technique. There were 1,998, 2,629, 3,112, and 3,054 differentially expressed genes (DEGs) at Days 7, 14, 21, and 28, respectively, during adipogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Whole transcriptional profiling of cellular metabolism during adipogenesis from MSC explored signaling pathways and metabolism of glucose, amino acid and fatty acid. It was shown that metabolism related pathways and the PI3K−Akt signaling pathway were the most enriched pathways using GO analysis ( Yi et al, 2020b ). The PI3K−Akt signaling pathway stimulated and directly regulated cellular metabolism by targeting the potential key genes, such as FASN, PCK1, SCD, and SLC2A1 and priming glucose aerobic glycolysis, arginine and proline metabolism, glutathione metabolism, and arachidonic acid metabolism during adipogenesis ( Yi et al, 2020b ).…”
Section: Gene Expression Profile In Adipogenesis Of Mscmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole transcriptional profiling of cellular metabolism during adipogenesis from MSC explored signaling pathways and metabolism of glucose, amino acid and fatty acid. It was shown that metabolism related pathways and the PI3K−Akt signaling pathway were the most enriched pathways using GO analysis ( Yi et al, 2020b ). The PI3K−Akt signaling pathway stimulated and directly regulated cellular metabolism by targeting the potential key genes, such as FASN, PCK1, SCD, and SLC2A1 and priming glucose aerobic glycolysis, arginine and proline metabolism, glutathione metabolism, and arachidonic acid metabolism during adipogenesis ( Yi et al, 2020b ).…”
Section: Gene Expression Profile In Adipogenesis Of Mscmentioning
confidence: 99%
“…It was shown that metabolism related pathways and the PI3K−Akt signaling pathway were the most enriched pathways using GO analysis ( Yi et al, 2020b ). The PI3K−Akt signaling pathway stimulated and directly regulated cellular metabolism by targeting the potential key genes, such as FASN, PCK1, SCD, and SLC2A1 and priming glucose aerobic glycolysis, arginine and proline metabolism, glutathione metabolism, and arachidonic acid metabolism during adipogenesis ( Yi et al, 2020b ). Also, analyzing polysomal RNA obtained after 3 days of adipogenic induction, it was indicated a change in the energetic profile in induced compared to non-induced cells ( Drehmer et al, 2016 ).…”
Section: Gene Expression Profile In Adipogenesis Of Mscmentioning
confidence: 99%
“…Aging is characterized by the gradual loss of physiological integrity in tissues that results in an increased risk of functional impairment and death. This degenerative process is a major risk factor for human diseases such as cancer, diabetes, and cardiovascular and neurodegenerative diseases 1,2 . Around 150 000 people die globally every day, of which about two‐thirds die from age‐related causes 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Proline (Pro) is a non-essential amino acid of particular relevance in mesenchymal cells, since it is needed for collagen synthesis and may play regulatory functions [36][37][38][39]. Due to its structural features, proline is a good substrate of SNAT transporters, which tolerate N-alkyl substitutions, but not of other sodium-dependent transporters, with the remarkable exception of the sodium-and chloride-dependent "IMINO" transporter SIT1 (SLC6A20, [24]) that, however, has a more restricted tissue-specific and development-dependent expression than SNAT transporters [40].…”
Section: Discussionmentioning
confidence: 99%